1996
DOI: 10.1177/070674379604100908
|View full text |Cite
|
Sign up to set email alerts
|

Étude du traitement des informations contextuelles syntaxiques lors d'une tâche de décision lexicale chez des sujets schizophrènes

Abstract: The results contrast with data on the processing of contextual semantic information by schizophrenic subjects, since the data in the literature conclude that there is an information-processing anomaly on the part of these patients. As a result, our study refutes the hypothesis of a generalized difficulty in the processing context by schizophrenic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
1
4
0
1
Order By: Relevance
“…We can assume that, under the experimental conditions used here, the process was used correctly by all the schizophrenic patients. These results confirmed the data of our first experiment in which a different lexical-decision paradigm was used (double lexical-decision task; Besche et al, 1996). These results are congruent with the data presented in the literature that indicate the preservation of syntactic processing during on-line tasks in schizophrenic participants (Carpenter, 1976;Miller & Phelan, 1980).…”
Section: Discussionsupporting
confidence: 91%
“…We can assume that, under the experimental conditions used here, the process was used correctly by all the schizophrenic patients. These results confirmed the data of our first experiment in which a different lexical-decision paradigm was used (double lexical-decision task; Besche et al, 1996). These results are congruent with the data presented in the literature that indicate the preservation of syntactic processing during on-line tasks in schizophrenic participants (Carpenter, 1976;Miller & Phelan, 1980).…”
Section: Discussionsupporting
confidence: 91%
“…This experiment was presented under two different conditions: a sequential presentation with a stimulus onset asynchrony (SOA) of 500 milliseconds as in the first experiment and a simultaneous presentation with an SOA of 0 milliseconds. The results revealed that only the semantic relations were ignored, while schizophrenia subjects processed the syntactic context normally, whatever the conditions of presentation (Besche et al 1996, 1997).…”
Section: Experimental Evidence In Favor Of Hardy-baylé’s Model: the P...mentioning
confidence: 88%
“…Unlike Frith [7], Hardy-Baylé and colleagues [8,62] suggest that the ability to attribute intention to others is intact in SCHI individuals. According to these authors, SCHI individuals' apparent inability to attribute intention to others is the result of their inability to use context to decode other people's intentions rather than a deficit in their ability to understand mental states.…”
Section: The Context Mis-processing Hypothesismentioning
confidence: 99%
“…Hardy-Baylé et al suggest an impairment of the inhibition mechanism to account for such a deficit. Disorganized SCHI subjects may able to process only syntactic context and not semantic or pragmatic context [62]. SCHI patients may fail to use context because they are unable to detect or encode contextually relevant information during comprehension [63,64].…”
Section: The Context Mis-processing Hypothesismentioning
confidence: 99%